Integrative analysis of metabolome and transcriptome reveals a dynamic regulatory network of potato tuber pigmentation - Yuhui Liu; Yuanming Li; Zhen Liu; Lei Wang; Kui Lin-Wang; Jinyong Zhu; Zhenzhen Bi; Chao Sun; Junlian Zhang; Jiangping Bai (iScience, 2023)
Summary: Potatoes consist of flavonoids that provide health benefits for human consumers. To learn more about how potato tuber flavonoid accumulation and flesh pigmentation are controlled, we analyzed the transcriptomic and metabolomic profile of potato tubers from three colored potato clones at three developmental phases using an integrated approach. From the 72 flavonoids identified in pigmented flesh, differential abundance was noted for anthocyanins, flavonols, and flavones. Weighted gene co-expression network analysis further allowed modules and candidate genes that positively or negatively regulate flavonoid biosynthesis to be identified. Furthermore, an R2R3-MYB repressor StMYB3 and an R3-MYB repressor StMYBATV involved in the modulation of anthocyanin biosynthesis during tuber development were identified. Both StMYB3 and StMYBATV could interact with the cofactor StbHLH1 and repress anthocyanin biosynthesis. Our results indicate a feedback regulatory mechanism of a coordinated MYB activator-repressor network on fine-tuning of potato tuber pigmentation during tuber development.